Discovering the Determining Parameters for the Photocatalytic Activity of TiO2 Colloids Based on an Anomalous Dependence on the Specific Surface Area. (7th August 2018) - Wintzheimer, Susanne; Szczerba, Wojciech; GuilhermeBuzanich, Ana; Kashiwaya, Shun; Klein, Andreas; Jaegermann, Wolfram; Toupance, Thierry; Shmeliov, Aleksey; Nicolosi, Valeria; Heuzé, Karine; Mandel, Karl; Dembski, Sofia
Abstract: The photocatalytic (PC) performance of titanium dioxide (TiO2 ) nanoparticles strongly depends on their specific surface, the presence of crystal defects, their crystal phase, and the exposed crystal facets. In order to understand which of these factors contributes most significantly to the PC activity of TiO2 colloids, all of them have to be individually analyzed. This study entails the synthesis of five anatase nanocrystal samples. By maintaining the same reactant ratios as well as hydrothermal sol–gel synthesis route and only varying the autoclaving time or temperature, different crystallite sizes are obtained under comparable experimental conditions. A decrease in PC performance with increase in specific surface area is found. Such an unexpected counterintuitive result establishes the basis for a better understanding of the crucial factors that ultimately determine the PC activity. These are investigated by studying nanocrystals bulk and surface structure and morphology using a selection of complementary analysis methods (X‐ray photoelectron spectroscopy (XPS), X‐ray absorption fine structure (XAFS), X‐ray diffraction (XRD)…). It is found that a change in the nanocrystal morphology from an equilibrium state truncated tetragonal bipyramid to a more elongated rod‐like structure accompanied by an increase in oxygen vacancies is responsible for an augmented PC activity of the TiO2 nanocrystals. Abstract : The photocatalytic performance of TiO2 nanoparticles depends amongst others on their specific surface, the presence of defects and the crystal facets. In this study anatase nanocrystals are synthesized showing an increase in photocatalytic performance during their growth, which is caused by a change in the nanocrystal morphology accompanied by an increase in oxygen vacancies.